Agricultural Communications Curriculum: Perceptions Of Ohio State Graduates - Barbara E. Cooper; Blannie E. Bowen (Journal of Applied Communications, 1989)
This study was designed to determine the perceptions of Ohio State University graduates regarding the agricultural communications curriculum. Specific objectives were to determine the graduates' demographic characteristics, satisfaction regarding the curriculum, and perceptions of academic experiences needed for future agricultural communicators. A mailed questionnaire went to 131 agricultural communications alumni. The response rate was 57. 1%. Ohio State agricultural communications graduates tend to be white females, who earned under 25,000. Graduates are satisfied with courses in agriculture and journalism/communications, and less satisfied with basic education requirements. For future agricultural communicators, graduates place more importance on journalism/communications classes than agriculture classes.